Understanding the continuance intention to learn using Google Classroom (GC) in online classes: decomposed technology acceptance model based / Mafarhanatul Akmal Ahmad Kamal … [et al.] - Ahmad Kamal, Mafarhanatul Akmal; Ramly, Bazrina; Zaraini, Noor Shariena; Mat Isa, Ilham Alia (Universiti Teknologi MARA, 2022)
Coronavirus pandemic has led to changes in the teaching and learning landscape. Both lecturers and students must accommodate the changes from face-to-face teaching and learning to online learning. This results in the various problems faced by both lecturers and students in online learning. Hence, many online platforms have been introduced to the field of education, such as Google Classroom, Edmodo, and Microsoft Teams. By pinning on the 12 factors in the decomposed technology acceptance model (DTAM) (i.e., perceived usefulness, perceived cognitive absorption, perceived ease of use, perceived internet self-efficacy, perceived computer self-efficacy, in-terpersonal influence, external influence, information quality, service quality, system quality, confirmation, and satisfaction) which are suggested by Roca et al. (2006), this research aims to investigate students’ continuance intention to learn with Google Classroom (GC) in online classes through the decomposed technology acceptance model. A 56-item questionnaire which covers the 12 factors of the decomposed technology acceptance model was administered to 242 undergraduate students from Universiti Teknologi MARA (UiTM); Puncak Alam and Shah Alam campuses. The statistical data of this research suggests that students’ continuance intention towards Google Classroom among UiTM students is high, which is influenced by the aforementioned factors. From these findings, this research is hoped to provide a new insight on the effectiveness of using GC in providing continuous interest in online learning among students.